Assimilation of satellite chlorophyll measurements into a coupled biophysical model of the Indian Ocean with a guided particle filter. Issue 5 (3rd May 2016) - Ratheesh, Smitha; Chakraborty, Abhisek; Sharma, Rashmi; Basu, Sujit
ABSTRACT: Satellite observations of surface chlorophyll have been assimilated into a coupled biophysical model of the Indian Ocean with particle filter (PF). Following the approach advocated in an earlier study, we have operated in a low-dimensional error subspace. Two different versions of PF have been implemented. In the traditional PF, the ensemble is augmented with two biological parameters, which are resampled along with state vector, followed by perturbation of the parameters with zero-mean Gaussian noise. In the other version, called guided PF, there is additional guidance of the ensemble towards future observations. While the traditional PF has not been able to outperform the standard run, the guided PF has been able to do so quite emphatically. This superior performance has been reflected in the time series of averaged chlorophyll in two sub-regions as well as in the spatial distribution of averaged chlorophyll in the same two sub-regions.